Diálogos entre a terapia cognitivo-comportamental e a psicanálise sobre o autismo. - Barreto, Lucila (2022)
The present study sets out to establish a dialogue between psychoanalytic theory and cognitive-behavioral therapy on autism in order to demonstrate the disagreements and possible approximations between them. To this end we describe psychoanalytic concepts of the English tradition, such as the psychic development of a baby and its relationship with the mother/carer and the facilitating environment (Winnicott, 1989), the development of the pychosome (Winnicott, 1949), facilitation of the emergence of the self objects (Klein, 1937) and the appearance of the desire for knowledge (Bion, 1967). In cognitive-behavioral therapy we describe the proposals of the ABA and TEACCH method, as well as the main features of the cognitivist approach . They have discussed autism as a question of cognitive deficit (Baron-Cohen, Leslie & Frith, 1985), emphasizing the discussions on the process of attention, memory, sensibility and stimuli of language. Despite the major distinctions regarding the scientific method, the way of caring therapeutically for the individuals with autism and the different expectations of cure, a possible articulation between psychoanalytic and cognitive-behavioral therapy can be established. For neuroscience and the discussions on the social brain (Laurentino, 2020), on the basis of the idea of the Theory of the Mind (ToM), we conclude that this may be a bridge between their two theories, respecting the profound differences.